Development of Novel Shortenings Structured by Ethylcellulose Oleogels. Issue 6 (20th May 2019) - Ye, Xiuyun; Li, Peixu; Lo, Y. Martin; Fu, Hong; Cao, Yanping
Abstract : Abstract: A novel shortening was developed based on oleogels structured by ethylcellulose (EC) polymers. The texture and oil retention ability of EC oleogels were characterized against the level of viscosity of different grades of EC, as well as the rheological properties in relation to the polymer structure in the gel network. EC100, which has an average viscosity of 100 cP, was selected as the most suitable organogelator at 4% (w/w) in combination with base oil (30% degree of saturation by mixing palm stearin and soybean oil) to form the shortening. Triglyceryl monostearate (TMS) was found to be the most effective emulsifier as evidenced by its ability to strengthen air‐incorporation ability of the shortening while creating evenly distributed fine crystals in the system. The EC100 shortening was able to create breads with excellent specific volume, indicating its ability to incorporate air bubbles during dough development and to serve as an antifirming agent to create bread with stable soft texture. Practical Application: In the present study, we attempted to create a novel shortening by employing oleogels structured by ethylcellulose (EC), the most promising gelation agent to develop gel network capable of replacing solid fat without health concerns. EC oleogels in shortening with detailed characterization of the shortening microstructure in relation to its functional properties was elucidated. The optimal formulation in relation to preservation of gel structure and consistency with enhanced moisture and air retention were also identified.